The Students’ Attitudes towards English Language Learning English Pedagogy Students, Faculty of Education, Souphanouvong University - VATHANAVONG , Phaivanh; LORTHACHANH, Thiam; KHAMMELEESAYSUE , Her; PANMANYVONG , Thavone; KHAMSAVANH, Dalavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This study aimed to evaluate students’ attitudes towards English language learning at Faculty of Education, Souphanouvong University and to compare the students’ attitudes towards English learning which categorized by year of study and areas of study. The samples were 90 students who majored in six areas of study at Faculty of Education, Souphanouvong University in the academic year 2019-2020 were randomly selected. In this study, the survey research was applied and questionnaire was utilized to collect information from the participants. The data was analyzed using SPPS Program, Version 24 and the data was displayed into Mean and Standard deviation. In order to compare students’ attitudes toward English learning, One-Way ANOVA was used to see the statistical differences. The results of the study showed that: 1). Overall, the students of the Faculty of Education have a low attitude towards English with an average of 2.39 and a standard deviation of 0.57, which indicates a negative attitude towards learning English. 2). To compare between year of study and subject areas, there were different attitudes towards English with a priority level of 0.01.